Penerepan aturan kaombo pada pengelolaan sumberdaya perikanan (Studi pengelolaan perikanan berbasis kearifan lokal) di Kelurahan Wali Kecamatan Binongko Kabupaten Wakatobi - Hasanuddin; Hamzah, Awaluddin; Mansyur, Akhmad (Jurnal Sosial Ekonomi Perikanan, 2021)
This study aims to determine how the Kaombo sanction for fisherman using destructive fishing and to find out how the Kaombo sanction for fisherman catching turtles. The research location was determined purposive with the consideration of an area that still applies Kaombo rules in fisheries resource management. The research method used descriptive qualitative method. The results showed that catching fish using destructive fishing gear is prohibited by Kaombo with a penalty of paying a fine of IDR 25,008,000 and catching turtles is prohibited by Kaombo with a penalty of paying a fine of IDR 600,000 per head.